KAJIAN SOSIOLOGI HUKUM TERHADAP KEPATUHAN HUKUM DI DALAM MASYARAKAT TENTANG KEHUTANAN - Fariq Fadhilla Widyatama; Mario Nazir Lumban Raja, M. Ridho Ramadani, Nopril Zaki Lidendra, Rendhy Arief Rahman (JOURNAL OF LAW AND NATION, 2024)
The environment is a part that is tied to human life, the environment contains animal habitats and the diversity of biodiversity within them, if the environment is damaged then this will destroy animal habitats and the diversity of biodiversity around them so that in the end it will cause the extinction of animals and biodiversity. the. Illegal logging or illegal logging results in direct or indirect changes to the physical characteristics and damage to sources of environmental biodiversity, resulting in environmental damage. The problem approach that will be used in this research is a normative juridical approach and an empirical approach. Law enforcement regarding environmental law as an effort for sustainable development must be implemented firmly, especially in cases of illegal logging. The regulations that regulate this matter are the promulgation of Law Number 41 of 1999 concerning Forestry which revokes the enactment of Law Number 5 of 1967. This was then changed to Law Number 19 of 2004 concerning the Determination of Government Regulations in Lieu of Law No. 1 of 2004 concerning Amendments to Law Number 41 of 1999 concerning Forestry. Apart from that, the government has also enacted Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction. Law enforcement is very important, therefore it is hoped that law enforcement officers in reducing cases of illegal forest logging may be able to provide information regarding the damage to the environment if illegal forest logging is carried out continuously to the community, or put up banners regarding prohibitions and sanctions. obtained from illegal logging activities or illegal logging. And it is hoped that the public can understand and comprehend the importance of the environment, let us protect the environment in order to achieve sustainable environmental development